Effects of cobalt oxide catalyst on pyrolysis of polyester fiber - Park, Chanyeong; Lee, Nahyeon; Cho, In Sun; Ahn, Byungmin; Yu, Hak Ki; Lee, Jechan (Korean Journal of Chemical Engineering, 2022)
Polyester fiber is a high-molecular-weight compound made from fossil fuels and is used in various synthetic fiber manufacturing processes. In this study, we performed non-catalytic and catalytic pyrolysis experiments using cobalt oxide as a catalyst to recover energy from polyester fiber. The experiment was carried out between 500–900 °C in the presence of N2. Amount of oil formation was the highest at 600 °C in non-catalytic pyrolysis and oil formation of catalytic pyrolysis was the highest at 500 °C. In both non-catalytic pyrolysis and catalytic pyrolysis, gas content was increased and char was decreased with increasing temperature. A marked difference was observed when the catalyst was used; the formation of char was suppressed and oil and gas yields increased. In the catalytic pyrolysis oil, benzoic acid compounds accounted for the largest proportion (16.15 wt%) at 900 °C, but polycyclic aromatic hydrocarbons and phenols were not observed. Benzoic acid is an important precursor material used to synthesize other organic substances, such as phenol and caprolactam. The non-condensable gas content increased from 11.55 wt% to 22.39 wt%, with increasing temperature. In particular, H2 gas yield was 4.44 wt% at 900 °C. Therefore, by using catalytic pyrolysis, high value-added chemicals such as benzoic acid compounds and H2 gas can be recovered at high yield at 900 °C from the polyester fiber. Consequently, unlike the existing treatment methods, the environmental impact of plastics can be reduced by catalytic pyrolysis.
Keywords: Catalytic Process; Plastic Waste; Pyrolysis; Reusable Energy; Thermochemical Process; Waste Treatment